Implementation of Game Based Learning Model to Improve Students' Speaking Skills in Indonesian Subjects at Madrasah Ibtidaiyah - Rahayu, Ninda; Salahudin, Anas; Rahman, Alvin Yanuar (UIN Siber Syekh Nurjati Cirebon, 2025)
This research is motivated by a problem regarding the low speaking skills of students in the learning process in Indonesian subjects in class IV-C MIN 2 Bandung City. The objectives are (1) to find out students' speaking skills before applying the Game Based Learning learning model in Indonesian subjects in class IV-C MI Negeri 2 Bandung City, (2) to find out the process of applying the Game Based Learning learning model in improving students' speaking skills in Indonesian subjects in class IV-C MI Negeri 2 Bandung City in each cycle and (3) to find out speaking skills students after applying the Game Based Learning learning model in Indonesian subjects in class IV-C MI Negeri 2 Bandung City at the end of the cycle. Using the Mixed Method approach, the Classroom Action Research (PTK) method is carried out in two cycles. The results of the study showed that there was an increase in speaking skills in each cycle. In the pre-cycle, classical completeness only reached 52% with an average of 62.59. After the action was taken, the results increased with classical completeness of 67% with an average score of 72.04 in cycle 1. Then it increased again in cycle 2 with classical completeness reaching 85% with an average score of 77.41. Thus, it can be concluded that the Game Based Learning learning model can improve students' speaking skills in Indonesian subjects in grades IV-C MIN 2 Bandung City. Keywords: Game Based Learning Model, Speaking Skills